Survival factor SvfA plays multiple roles in differentiation and is essential for completion of sexual development in Aspergillus nidulans - Lim, Joo-Yeon (Sci Rep, 2020)
The first member of the velvet family of proteins, VeA, regulates sexual development and secondary metabolism in the filamentous fungus Aspergillus nidulans. In our study, through comparative proteome analysis using wild type and veA-deletion strains, new putative regulators of sexual development were identified and functionally analyzed. Among these, SvfA, containing a yeast survival factor 1 domain, plays multiple roles in the growth and differentiation of A. nidulans. Deletion of the svfA gene resulted in increased sensitivity to oxidative and cold stress as in yeast. The svfA-deletion strain showed an increase in bi-polar germination and a decrease in radial growth rate. The deletion strain formed structurally abnormal conidiophores and thus produced lower amounts of conidiospores during asexual development. The svfA-deletion strain produced few Hülle cells and small cleistothecia with no ascospores, indicating the requirement of svfA for the completion of sexual development. Transcription and genetic analyses indicated that SvfA modulates the expression of key development regulatory genes. Western blot analysis revealed two forms of SvfA. The larger form showed sexual-specific and VeA-dependent production. Also, the deletion of svfA caused decreased ST (sterigmatocystin) production. We propose that SvfA is a novel central regulator of growth, differentiation and secondary metabolism in A. nidulans.